Hubungan Antara Kebiasaan Berpikir Negatif Tentang Tubuh Dengan Body Esteem dan Harga Diri - Herabadi, Astrid Gisela (UI Scholars Hub, 2007)
A considerable body of research has acknowledge the relationship between body esteem and the more general self esteem, however not much has been revealed concerning the dynamic process of self esteem development.The following research was intended to: (1) identify the predictors of low body esteem, and (2) how these predictors and body esteem itself consequently contribute to low self esteem. Participants were 458 college students in Atma Jaya Catholic University Jakarta (229 males and 229 females), they responded to a set of questionnaire that includes scales to measure BMI (Body Mass Index); subjective evaluation (satisfaction) on one’s own body; negative thinking habit about one’s own body; body esteem; and self esteem. Analyses revealed that only satisfaction on one’s own body; negative thinking habit about one’s own body; and BMI predicted body esteem. However, individual’s subjective evaluation contribute more in the development of self esteem compared to the more objective measure of body proportion such as the BMI. Consequently, body esteem and negative thinking habit about one’s own body predicted the more general self esteem. Results highlight the importance of negative habit of self thinking about one’s own body — rather than BMI, the more objective measure of body proportion — in predicting body esteem; and another imperative conclusion is that negative habit of self thinking about one’s own body has a direct contribution to predict general self esteem, unlike satisfaction on one’s own body which only contribute to self esteem through the mediation of body esteem.